Melokalkan Agenda Global: Peran Aktor di Daerah dalam Adaptasi Tujuan Pembangunan Berkelanjutan (TPB) / Sustainable Development Goals (SDGS) di Indonesia - Nino Viartasiwi (Majalah Ilmiah DIAN ILMU, 2022)
As a series of global agendas, the Sustainable Development Goals (SDGs) aim to become the compass for development throughout the world. Local governments are the spearhead of implementing SDGs at the local level. This study presents possible challenges faced by regional actors in localizing the global agenda to help local governments adapt the implementation of the SDGs. The purpose of this study is to draw lessons from the empirical experiences of actors in the regions in adapting to global goals at the local level without leaving the potential and uniqueness of the region. This study describes the case of local adaptation, especially the attitude of actors towards the SDGs experienced by three local governments in East Java Province, Indonesia, namely: Jember Regency, Bondowoso Regency and Situbondo Regency. The research method used is qualitative through in-depth interviews and literature study. The findings in this study are divided into two, namely a situation description of adaptation and challenges faced by actors in actualizing the SDGs in the local context. This study underlines that the efforts of local actors in adapting the SDGs have been adequate, but at the same time several challenges have been found such as the low understanding of the SDGs values from state apparatus, weak budget, political will of local actors, and local political dynamics.